Why Tourist Destinations Are Hard to Survive After Disaster? Case Study of Communication Barrier in the Tanjung Lesung Special Economic Zones (SEZ) Stakeholders - Sophia Novita; Firmansyah Firmansyah; Ashabul Yamin Asgha (Jurnal Riset Komunikasi (JURKOM), 2023)
Tanjung Lesung’s Special Economic Zones (SEZ) is a tourist destination developed as a coastal tourism potential in Indonesia. The development of the Tanjung Lesung SEZ experienced challenges when the natural tsunami disaster in 2018 caused the Tanjung Lesung tourism slump. Research on communication between stakeholders is essential to determine how each stakeholder plays his role and coordinates with each other to revive tourism in particular economic areas. This study aims to analyze the problem of communication among tourism area stakeholders. The research uses a case study method with the object being the Tanjung Lesung tourism SEZ. The research subjects are the stakeholders of the tourism area. Data were collected by observation and conducting semi-structured interviews with 17 informants from four types of stakeholders: local governments, private companies, media, and community groups in the buffer zone. The data is also complemented by an academic review of the literature. Data analysis uses analysis with a stakeholder theory approach, which looks at the relationship between stakeholders in realizing common goals in developing particular economic areas for tourism. The results showed communication gaps among stakeholders, with each stakeholder having their strategy for developing tourism. The tourism strategy has not been integrated with all stakeholders due to internal conflicts in the management of the Tanjung Lesung area and its supporting areas. Stakeholders need to communicate regularly and work together to determine the target market so there is no gap between stakeholders in carrying out tourism development strategies after the disaster.